Characteristics of subclinical pulmonary tuberculosis compared to active pulmonary tuberculosis: A retrospective cohort study - Aiping Zhang; Wenjie Wang; Zijian Wang; Haoyu Sheng; Jianghua Yang (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2025)
Background: Little is known about subclinical pulmonary tuberculosis (SPTB), and its diagnosis remains challenging. The aim is to analyze the results of laboratory of SPTB and improve clinical understanding and help early diagnosis. Method: This retrospective cohort study was conducted in patients with pulmonary tuberculosis (TB) at a university hospital in China. 138 cases of SPTB were compared with active pulmonary tuberculosis (APTB) (140 cases) and healthy person (HC) (136 cases). Result: The average age of the SPTB group (40.43 ± 19.85 years) was younger than that of the APTB group (50.01 ± 21.49 years) (p < 0.05). The WBC count was elevated in both pulmonary TB groups compared to the HC group(p < 0.05). CRP and CA-125 were higher in the APTB group than in SPTB and HC group (p < 0.05). The CD4+ T cells counts in SPTB group was lower than that in HC group (p < 0.05); although the CD4+ T cells counts in SPTB group was lower than that in APTB group, the difference was not statistically significant (p > 0.05). There were statistically significant differences in CD8 + T cells counts between the three groups (p < 0.05), and the CD8 + T cells counts in two pulmonary TB groups was lower than that in the HC group (p < 0.05), and there was no statistically significant difference between SPTB and APTB group (p > 0.05). The T-SPOT.TB value in SPTB were lower than those in the APTB group (p < 0.05). Conclusion: Patients with SPTB tend to develop the condition at a younger age and are predominantly male. Clinically, we can judge whether SPTB will develop into APTB by monitoring WBC count, CA-125, CRP, T lymphocyte count and T-SPOT.TB value level, in order to achieve the purpose of early diagnosis and treatment.